Role of personal aptitudes as determinants of incident morbidity, lifestyles, quality of life, use of health services, and mortality (DESVELA cohort): quantitative study protocol for a prospective cohort study in a hybrid analysis - Martí-Lluch, Ruth; Bolíbar, Bonaventura; Llobera, Joan; Maderuelo-Fernández, José A; Magallón-Botaya, Rosa; Sánchez-Pérez, Álvaro; Fernández-Domínguez, Ma José; Motrico, Emma; Vicens-Pons, Enric; Notario-Pacheco, Blanca; Alves-Cabratosa, Lia; Ramos, Rafel; et al. (Frontiers in Public Health, 2023)
Background The healthcare and well-being of persons depend on multiple factors and should adapt to societal changes. The opposite is also occurring; society has evolved concerning the individuals’ approach to their care, including participation in decision-making processes. In this scenario, health promotion and prevention become essential to provide an integrated perspective in the organisation and management of the health systems. Health status and well-being depend on many aspects, determinants of health, which in turn may be modulated by individual behaviour. Certain models and frameworks try to study the determinants of health and individual human behaviours, separately. However, the interrelation between these two aspects has not been examined in our population. Our main objective is to analyse whether personal aptitudes related to behaviours are independently associated with the incidence of morbidity. A secondary objective will enquire whether these personal aptitudes are independently associated with lower all-cause mortality, enhanced adoption of healthy lifestyles, higher quality of life, and lower utilization of health services during follow-up. Methods This protocol addresses the quantitative branch of a multicentre project (10 teams) for the creation of a cohort of at least 3083 persons aged 35 to 74 years from 9 Autonomous Communities (AACC). The personal variables to evaluate are: self-efficacy, activation, health literacy, resilience, locus of control, and personality traits. Socio-demographic covariates, social capital, and community health assets will be recorded. A physical examination, blood analysis, and cognitive evaluation will be carried out. Several sets of six Cox models (one for each independent variable) will analyse the incidence of morbidity (objective 1), all-cause mortality, and the rest of the dependent variables (objective 2). The models will be adjusted for the indicated covariates, and random effects will estimate Potential heterogeneity between AACC. Discussion The analysis of the association of certain behavioural patterns and determinants of health is essential and will contribute to improving health promotion and prevention strategies. The description of the individual elements and interrelated aspects that modulate the onset and continuance of diseases will allow the evaluation of their role as prognostic factors and contribute to the development of patient-tailored preventive measures and healthcare.